Integrated Decision-making Method in Performance Evaluation and Rating of Recreational-Sports Pools - Abdolhamid Jamali; Mehdi Salimi; Davoud Nasr Esfahani (Shahid Bahonar University of Kerman, 2022)
The present study is implemented to identify indicators and to provide an optimal evaluation method in recreational-sports pools. The present study is considered practical in purpose, and survey in collecting data. Firstly, by bibliometric research and five professional experts' interviews, 91 indicators were identified for evaluating recreational-sports pools. Secondly, in terms of 4 components or perspectives in the Balanced Scorecard, 57 indicators were established (internal processes (10 indicators), customer (22 indicators), growth and learning (19 indicators), and financial (6 indicators)), from focal group's output which was comprised of 4 prominent professors. The structure was confirmed based on 333 individuals' opinions in the statistical population by employing factor analysis. In order to rate the pools studied, the gray clustering analysis method was applied followed by the structure of the balanced scorecard confirmed. Principally, 20 homogenous recreational-sports pools were investigated in 15 city regions and boundaries of provinces in Isfahan, Sepahan Shahr, and Baharestan. Based on data analysis and rating of each case study, Araman, Absar, Enghelab, Morvarid, and Golsar pools were ranked first to fifth, respectively. Furthermore, the main purpose of the present study based on calculated indicators is to propose a practical method to provide an accurate evaluation of sports pools.